Tanggung Jawab Pemerintah Terhadap Perlindungan Satwa Liar Di Kabupaten Kepulauan Aru - Bugis, Indiyani; Pietersz, Jemmy Jefry; Rugebregt, Revency Vania (Bacarita Law Journal, 2023)
Protected animals are animals that are protected by public authorities or the government. Therefore, the local community cannot take actions that violate the provisions set by the public authorities for these wild animals. Basically, Indonesia is an archipelagic country which is famous for its diversity of endangered species protected by public authorities and is also an environment for endemic creatures, which means that it has its own characteristics in each area and cannot be found in other areas. Legally the government's efforts to protect wild animals from the threat of extinction are carried out by issuing the previously mentioned laws and regulations, namely Law Number 5 of 1990 concerning Conservation of Living Natural Resources and Their Ecosystems, followed by the enactment of Government Regulation Number 13 of 1994 concerning Hunting for Wildlife, Government Regulation Number 68 of 1998 concerning Nature Reserve Areas and Nature Conservation Areas, and Government Regulation Number 7 of 1999 concerning Preservation of Plant and Animal Species, as well as Government Regulation Number 8 of 1999 concerning Utilization of Plant and Animal Species. With clear rules, law enforcement can work more effectively to protect animals, especially wild animals.